Guidelines for identification and treatment of individuals with attention deficit/hyperactivity disorder and associated fetal alcohol spectrum disorders based upon expert consensus - Young, S.; Absoud, M.; Blackburn, C.; Branney, P.; Colley, B.; Farrag, E.; Fleisher, S.; Gregory, G.; Gudjonsson, G.; Kim, K.; O'Malley, K.; Plant, Moira; et al. (BioMed Central Ltd., 2016)
Background: The association of attention deficit/hyperactivity disorder (ADHD) and fetal alcohol spectrum disorders (FASD) results in a complex constellation of symptoms that complicates the successful diagnosis and treatment of the affected individual. Current literature lacks formal guidelines, randomized control trials, and evidence-based treatment plans for individuals with ADHD and associated FASD. Therefore, a meeting of professional experts was organized with the aim of producing a consensus on identification and treatment guidelines that will aid clinicians in caring for this unique patient population. Methods: Experts from multiple disciplines in the fields of ADHD and FASD convened in London, United Kingdom, for a meeting hosted by the United Kingdom ADHD Partnership (UKAP; www.UKADHD.com) in June 2015. The meeting provided the opportunity to address the complexities of ADHD and FASD from different perspectives and included presentations, discussions, and group work. The attendees worked towards producing a consensus for a unified approach to ADHD and associated FASD. Results: The authors successfully came to consensus and produced recommended guidelines with specific regards to identification and assessment, interventions and treatments, and multiagency liaisons and care management, highlighting that a lifespan approach to treatment needs to be adopted by all involved. Included in the guidelines are: 1) unique ‘red flags’, which when identified in the ADHD population can lead to an accurate associated FASD diagnosis, 2) a treatment decision tree, and 3) recommendations for multiagency care management. Conclusions: While clinically useful guidelines were achieved, more research is still needed to contribute to the knowledge base about the diagnosis, treatment, and management of those with ADHD and associated FASD.